Effects of Monetary Policy on Inflation and National Economy Based on Analysis of Bank Indonesia Annual Report - Angelina, Silvia; Nugi Mohammad Nugraha (Technium Social Sciences Journal, 2020)
This study focuses on analysis (1) money supply effect, previous period money supply, the level of SBI (Bank Indonesia Certificate), the exchange rate, and the economy on inflation in Indonesia (2) The effect of inflation, domestic investment, previous period domestic investment, foreign investment, previous period foreign investment, and economic labor in Indonesia. Time series data using the simultaneous analysis model equation of the Two-Stage Least Squared (TSLS) method. The results of the study concluded that (1) the money supply had a significant and positive impact on inflation, the money supply in the previous period had a significant and positive impact on inflation, the SBI rate had a significant and negative effect on inflation, the exchange rate had a significant and positive effect on inflation. Meanwhile, the national economy has no significant and positive effect on inflation. If the money supply increases, inflation will increase. If the money supply in the previous period increased, inflation would also increase. If the SBI interest rate rises, inflation will depreciate. If the exchange rate rises, inflation will appreciate. If the level of the national economy rises, inflation will appreciate. (2) Domestic investment, previous period domestic investment, foreign investment, previous period foreign investment, and labor have a significant effect on the economy in Indonesia, while the inflation rate has no significant effect on the economy in Indonesia